A peak into metastatic Leydig cell tumor: a rare case report - Bhandari, Hitesha; Patil, Ashwini M.; Pawar, Prathamesh M.; Bagul, Kiran G.; Pawar, Suraj B.; Nilapwar, Rishikesh D.; Pawar, Aditya S. (International Journal of Research in Medical Sciences, 2024)
Testicle tumors are a rare entity among men population, comprising 1-1.5% of all cancers. The Sex cord Stromal tumors contribute just 4% of all testicular cancers, only 10% of them are malignant. Most common sex cord-stromal tumors are the Leydig cell tumor, comprising of 75 to 80% of the total. Incidence is bimodal involving children and adults between 30 and 60 years. The commonest metastatic sites are regional lymph nodes, lung, liver, and bones. Here, we report a case of late metastatic relapsed Leydig cell tumor in a 38-year-old male. Patients with metastatic Leydig cell tumors have poor prognosis and standard treatment recommendations are unclear.